KELEMBAGAAN PENDIDIKAN SULUK DI KABUPATEN KAMPAR (TINJAUAN FUNGSI MANAJEMEN) - Hairi Padhol; Isjoni Isjoni; Daeng Ayub Natuna (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2018)
This study was a qualitative research. The thoug collection was done withtechnical documentation, observation and interviews. Objective (1) To know planning in instituteof suluk, (2) To know management in institute of suluk, (3) To know organization in institute ofsuluk, (4) To know observation in institute of suluk, (5) To know follow-up in institute of suluk.Institute education of suluk one of the informal education system. Of cours, owning separateprocedures and oder in management execution it, including into management education of suluk.Suluk management below/ naqsabandi tarikat head as tarikat head executor have the followingladder : someone which have been permitted to lead suluk dubed by Mursyid while undermursyid proxy and under referred as tarikat khalifah, while head as a whole and becomemursyid from entire referred as Mursyid Syaidul. Usually in mursyid lifing after executin educationof suluk, diploma mursyid syaidul perform mursyid, mursyid proxy and tarikat khalifa to peoplewho assumed competent and fulfil its condition. Each time suluk is sometimes lifted by twomursyid people, three mursyid proxy people and a number of khalifa as according to itsrequirement. Education decentralization give to education institute and local society to processeducation. Thereby can be expected reaching of productivity and quality education of it self.This matter also form independence institute education.